Cytochrome P450 and the immune response to prolonged administration of isoniazid, nevirapine and paracetamol in a rat model - Bekker, Zanelle (University of the Free State, 2015)
Drug-induced liver injury is a major adverse drug reaction that presents during isoniazid (INH) and nevirapine (NVP) treatment, and after paracetamol (PAR) overdose. It was postulated that after these drugs are metabolised, reactive metabolites are formed which attack cellular proteins and result in the formation of antigenic metabolite-protein adducts. Subsequently, the immune system starts to eliminate hepatocytes expressing these adducts, and this leads to the development of overt drug-induced liver injury. As such, the effect of prolonged administration of INH, NVP and PAR on the cytochrome P450 (CYP450) and immune response was investigated here. A high performance liquid chromatography (HPLC) method for the simultaneous determination of INH, NVP and PAR in plasma was developed. Sample preparation involved protein precipitation with zinc sulphate and methanol, followed by solid phase extraction. The mobile phase was 0.06% trifluoroacetic acid (A) and acetonitrile (B) and run by a gradient programmer over a C18 (4.60 x 250 mm) 5 μ analytical column at 1 ml/min, while the eluent was detected by UV at 260 nm. INH, PAR, internal standard and NVP eluted at retention times of 3.1, 9.9, 10.6 and 11.6 minutes, respectively. The average 5 day calibration curves of INH, NVP and PAR were linear with regression equations and correlation coefficients of y = 0.029x + 0.025 (r2 = 0.9954), y = 0.043x + 0.127 (r2 = 0.9968) and y = 0.097x + 0.070 (r2 = 0.9997), respectively. The method was used successfully to monitor INH, NVP and PAR in rat plasma. The CYP450 and immune response to prolonged administration of INH, NVP and PAR were investigated using an SPD rat model. For each drug, the animal experiment was divided into three phases. In phase I, rats were orally administered saline solution (S), INH (20 mg/kg), NVP (200 mg/kg) or PAR (500 mg/kg), while for phase II, rats received S, INH, NVP or PAR in combination with an immune stimulant, levamisole (LMS; 2.5 mg/kg), and lastly, during phase III, rats received S, INH, NVP or PAR along with a CYP450 inducer, carbamazepine (CBZ; 60 mg/kg). In each phase, five rats per group were sacrificed after 2, 7, 14, 28 and 42 days. Blood was analysed for full blood count, CD4 and CD8 counts, liver function, renal function, IL-2, IL-10, IgG, IgM and drug concentrations. A piece of liver was sent for histopathology testing, and the activity of rat CYP1A2, CYP2E1 and CYP3A2 were analysed. During administration of the test drugs alone, both INH and NVP triggered an early Th1 immune response that was associated with liver injury, and counteracted by a later Th2 immune response which was associated with healing. Overall, the liver injury correlated with low concentrations of NVP, but high INH concentrations. That said, INH increased CYP2E1 activity, while NVP increased that of CYP3A2. When LMS (immune stimulant) was co-administered, INH liver injury was exacerbated, while for NVP it was the same. Again, INH and NVP provoked a Th1 response (injury) that was counteracted by a Th2 response (healing). Here, the liver injury was also associated with low NVP concentrations, and high INH concentrations. During co-administration of CBZ (CYP450 inducer), INH and NVP caused the same immune response, and resulted in improvement of the liver injury. Again, the liver injury was associated with low NVP concentrations, and high INH concentrations. Also, INH increased CYP2E1 activity and NVP increased CYP3A2 activity, but not to the same extent as the test drugs alone. PAR did not exhibit a distinct pattern of immune response by which to associate it with the liver injury, most probably because the concentrations were too low for generation of toxic metabolites. In conclusion, the pattern of immune response to prolonged administration of INH and NVP shows that the immune system is involved in the drug-induced liver injury, probably as a protective buffer to prevent further drug toxicity.

Middel-geïnduseerde lewerskade kom algemeen voor tydens isoniasied (INH) en nevirapien (NVP) behandeling en na parasetamol (PAR) oordosering. Dit is voorgestel dat ná metaboliese aktivering van die middels, reaktiewe metaboliete gevorm word wat sellulêre proteïene aanval en daardeur antigeniese metabolietproteïen neweprodukte vorm. Gevolglik word die immuunsisteem gestimuleer om hepatosiete te verwyder wat uitdrukking gee aan dié neweprodukte en dit lei tot waarneembare hepatotoksisiteit. Dus is die sitochroom P450 (CYP450) en immuunrespons van langtermyn toediening van INH, NVP en PAR hier ondersoek. Eerstens is `n hoëdrukvloeistof-chromatografie (HPLC) metode vir die gelyktydige bepaling van INH, NVP en PAR in plasma ontwikkel. Monstervoorbereiding het behels proteïenbesinking met sinksulfaat en metanol, gevolg deur vaste fase ekstraksie. Die mobiele fase het bestaan uit 0.06% trifloroasetaatsuur (A) en asetonitriel (B) en is gechromatografeer met `n gradiënt programmeerder deur `n C18 (4.60 x 250mm) 5μ analitiese kolom teen 1ml/min, terwyl die eluaat bepaal is deur UV teen 260nm. INH, PAR, die interne standard en NVP het onderskeidelike retensietye van 3.1, 9.9, 10.6 en 11.6 minute gehad. Die onderskeie, gemiddelde 5 dag kalibrasiekromme van INH, NVP en PAR het liniêre regressievergelykings en korrelasie-koëffisiënte van y = 0.029x + 0.025 (r2 = 0.9954), y = 0.043x + 0.127 (r2 = 0.9968) en y = 0.097x + 0.070 (r2 = 0.9997) gehad. Die metode is suksesvol gebruik om INH, NVP en PAR in behandelde rotte te bepaal. Die CYP450 en immuunrespons van langtermyn toediening van INH, NVP en PAR is bestudeer in `n SD rotmodel en die diereëksperiment is verdeel in drie fases. In fase I is die rotte oraal gedoseer met soutoplossing (S), INH (20mg/kg), NVP (200mg/kg) of PAR (500mg/kg). In fase II is die rotte doseer met S, INH, NVP of PAR in kombinasie met `n immuunstimulant, levamisool (LMS; 2.5mg/kg) en tydens fase III het rotte S, INH, NVP of PAR ontvang saam met `n CYP450-induseerder, karbamasepien (CBZ; 60mg/kg). Vyf rotte per groep is geslag na 2, 7, 14, 28 en 42 dae. Bloed is getoets vir volbloedtelling, CD4 en CD8 tellings, lewerfunksie, nierfunksie, IL-2, IL-10, IgG, IgM en middelkonsentrasies. `n Lewermonster is gestuur vir histopatologiese ondersoek en die aktiwiteit van rot CYP1A2, CYP2E1 en CYP3A2 bepaal. Tydens toediening van die toetsmiddels op hul eie, het beide INH en NVP `n vroeë Th1 immuunrespons ontlok wat verbind kon word met lewerskade. Die reaksie is teengewerk deur `n latere Th2 immuunrespons wat verbind kon word met herstel. In die geheel het die lewerskade gekorreleer met lae konsentrasies van NVP, maar hoë INH-konsentrasies. Verder het INH CYP2E1 aktiwiteit verhoog, terwyl NVP dié van CYP3A2 verhoog het. Waar LMS (immuunstimulant) gelyktydig toegedien is, is INH-lewerskade vererger, maar vir NVP was die lewerskade onveranderd. Weereens het INH en NVP `n Th1 respons (lewerskade) ontlok wat teengewerk is deur `n Th2 respons (herstel). Hier kon die lewerskade ook verbind word met lae NVP-konsentrasies en hoë INHkonsentrasies. Tydens die gelyktydige toediening van CBZ (CYP450-induseerder), het INH en NVP dieselfde immuunrespons veroorsaak wat gelei het tot verbetering van die lewerskade. Weereens kon die lewerskade verbind word met lae NVP-konsentrasies en hoë INH-konsentrasies. Hier het INH CYP2E1 aktiwiteit verhoog en NVP het CYP3A2 aktiwiteit verhoog, maar nie tot die volle omvang soos met die toetsmiddels op hulle eie nie. PAR het nie `n onderskeibare immuunresponspatroon ten toon gestel wat met die lewerskade verbind kon word nie, heel waarskynlik omdat die konsentrasies te laag was om toksiese metaboliete te vorm. Gevolglik het die immuunresponspatroon van langtermyn toediening van INH en NVP gewys dat die immuunsisteem betrokke is by middel-geïnduseerde lewerskade, waarskynlik as `n beskermende buffer om verdere middeltoksisiteit te voorkom.
Dissertation (M.Med.Sc. (Pharmacology))--University of the Free State, 2015
Keywords: Isoniazid; Nevirapine; Paracetamol; Prolonged administration; Liver injury; Immune response; Cytochrome P450; HPLC; Pharmacology, experimental; Liver -- Wounds and injuries; Rats -- Experiments; Drug -- Testing.